2017
DOI: 10.1016/j.euroecorev.2016.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic experiences and risk taking of euro area households

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 44 publications
4
25
1
Order By: Relevance
“…Households with heads at the early stages of the lifecycle appear to be less inclined to hold high risk assets, as is also the case for being non-white and having relatively low levels of education. These effects accord with intuition as well as the existing literature (see, e.g., Guiso et al, 1996;Guiso and Paiella, 2008;Ampudia and Ehrmann, 2017). 4 Active versus inactive investors…”
Section: Modelling Asset Shares In Household Portfoliossupporting
confidence: 87%
See 1 more Smart Citation
“…Households with heads at the early stages of the lifecycle appear to be less inclined to hold high risk assets, as is also the case for being non-white and having relatively low levels of education. These effects accord with intuition as well as the existing literature (see, e.g., Guiso et al, 1996;Guiso and Paiella, 2008;Ampudia and Ehrmann, 2017). 4 Active versus inactive investors…”
Section: Modelling Asset Shares In Household Portfoliossupporting
confidence: 87%
“…There are a small number of studies that consider the role of the underlying macroeconomic and financial conditions but they do not investigate the effects of monetary policy. Such studies have found that risk preferences, in general, and household asset allocation in particular, are linked to the economic environment (Christelis et al, 2013), business cycle fluctuations (Bucciol and Miniaci, 2015), and exposure to past economic and financial crises (Malmendier and Nagel, 2011;Ampudia and Ehrmann, 2017). The empirical findings in this paper are in line with monetary policy shocks exerting an important effect on risk preferences even after controlling for micro-characteristics and macro-conditions.…”
Section: Introductionsupporting
confidence: 79%
“…Their main finding is that individuals who lived during periods of low stock market returns report lower willingness to bear risk and, consistently, are less likely to hold risky financial assets, while realized volatility has no significant impact on household portfolio choice. Ampudia and Hermann () confirm their results for a set of European countries. Due to the lack of panel data, Malmendier and Nagel () were unable to distinguish between individuals whose portfolio was only marginally affected by the poor stock market performance (because of their negligible investments in equity), and those whose financial wealth was seriously exposed to stock market risk.…”
Section: Literature Reviewmentioning
confidence: 53%
“…A possible explanation is that the stock market return series I use is much shorter than theirs, and does not include the years of the Great Depression. Ampudia & Ehrmann (2014) replicate the Malmendier and Nagel study for the Eurozone-including the Netherlands-and do find that experienced stock market returns affect risk aversion and stock holding. All regressions include the following variables: individual fixed effects, year dummies, age and age squared partner, city, education dummies, dummies for occupation status, and the presence of children in the household.…”
Section: Risk Attitudesmentioning
confidence: 60%